The effect of the external factors on the students' acceptance of virtual learning in universities of Saudi Arabia - Aleshidi, Hamad Aedh; Ramdane, Tahraoui (Institute of Information System & Research Center ( IISRC), 2012)
The rapidly growing popularity of E-Learning has introduced new terms to education, such as Virtual Classroom. In line with the technological development, the Saudi Arabia University education received generous financial and technical support to integrate education with ICT. ICT facilities have been provided at public universities as well as the private ones in Saudi Arabia. Along with the benefits that increasing technological options can provide, there are still many barriers to the successful integration and usage of emerging educational technology within educational environments. Many researches had indicated some factors that could influence the students' acceptance of virtual learning in Saudi Arabia, but they not well confirmed yet, therefore, this study adopted TAM model to predicted the effect of the external factors: perceived of peer encouragement(PPE), cultural factors (CF), computer self-efficacy(CSE) and enjoyment (EN) the undergraduate students’ acceptance of virtual learning. 400 participants from two public universities were framed the sample of the study, the researcher had developed virtual classroom to implement this study. For hypotheses testing, SEM results showed that the TAM model was applicable, valid and reliable to indicate the students' acceptance in Saudi universities; furthermore, the four examined factors have significantly contributed to the students' acceptance of virtual learning.